AKURASI DIAGNOSTIK DENGAN MENGGUNAKAN BIOMARKER METILASI DNA DALAM DETEKSI DINI KANKER PARU: TINJAUAN SISTEMATIS - Solihat Nur Alifia (2023)
Lung cancer is a malignant disease in the lung, including primary malignancy and malignancy from outside the lung in the form of metastasis. Early lung cancer screening methods still have many weaknesses that can cause high incidence and mortality in lung cancer today, so an effective early detection method is needed. DNA methylation examination using the SHOX2 biomarker is considered to have advantages over other biomarkers. The study aims to determine the diagnostic accuracy of SHOX2 biomarkers in detecting early lung cancer, including sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV). The research design was a systematic review with pooled data. The literature search was conducted on five different journal databases using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) 2020 method covering articles from 2012-2022. Eighteen studies met the inclusion criteria. The results showed that the SHOX2 biomarker had a sensitivity value of 81.84% (95% CI, 78.91-84.52%), a specificity value of 82.38% (95% CI, 79.72-84.83%), a PPV value of 79.85% (95% CI, 77.40-82.09%) and an NPV value of 84.17% (95% CI, 82.01-86.12%). Based on its diagnostic accuracy, SHOX2 biomarker is not recommended as a primary diagnostic tool, but it can support the diagnosis after examination using Low Dose CT Scan (LDCT) to reduce the false positive rate.